Constraining groundwater flow in the glacial drift and saginaw aquifers in the Michigan Basin through helium concentrations and isotopic ratios. Issue 1 (23rd March 2015) - Wen, T.; Castro, M. C.; Hall, C. M.; Pinti, D. L.; Lohmann, K. C.
Abstract: 3 He and 4 He concentrations in excess of those in water in solubility equilibrium with the atmosphere by up to two and three orders of magnitude are observed in the shallow Glacial Drift and Saginaw aquifers in the Michigan Basin. A simplified He transport model shows that in situ production is negligible and that most He excesses have a source external to the aquifer. Simulated results show that 3 He and 4 He fluxes entering the bottom of the Saginaw aquifer are 7.5 × 10 −14 and 6.1 × 10 −7  cm 3 STPcm −2  yr −1, both of which are lower than fluxes entering the underlying Marshall aquifer, 1.0 × 10 −13 and 1.6 × 10 −6 cm 3 STPcm −2  yr −1 for 3 He and 4 He, respectively. In contrast, He fluxes entering the Saginaw aquifer are higher than fluxes entering the overlying Glacial Drift aquifer of 5.2 × 10 −14 and 1.5 × 10 −7  cm 3 STPcm −2  yr −1 for 3 He and 4 He, respectively. The unusually high He fluxes and their decreasing values from the lower Marshall to the upper Glacial Drift aquifer strongly suggest the presence of an upward cross‐formational flow, with increasing He dilution toward the surface by recharge water. These fluxes are either comparable to or far greater than He fluxes in deeper aquifers around the world. Model simulations also suggest an exponential decrease in the horizontal groundwater velocity with recharge distance. Horizontal velocities vary from 13 to 2 myr −1 for the Saginaw aquifer and from 18 to 6 myr −1 for the Marshall aquifer. The highly permeable Glacial Drift aquifer displays a greater velocity range, from 250 to 5 myr −1 . While Saginaw 4 He ages estimated based on the simulated velocity field display an overall agreement with 14 C ages, 14 C and 4 He ages in the Glacial Drift and Marshall aquifers deviate significantly, possibly due to simplifications introduced in the He transport model leading to calculation of first‐order approximation He ages and high uncertainties in Glacial Drift 14 C ages.